Emergency preparedness and health system resilience assessment tool: development and initial validation - Vageesh Jain; Fadi El-Jardali; Michael Reid; Sherin Varkey; Racha Fadlallah; Denizhan Duran; Priyanka D Kanth; Son-Nam Nguyen; Rekha Menon; Ammar Malek; Majd Saleh; Laura Buback (BMJ Global Health)
Background Middle East and North Africa (MENA) region has been one of the most significantly impacted by the COVID-19 pandemic. The escalating frequency and complexity of global health threats—from pandemics like COVID-19 to climate change-induced emergencies—have elevated the imperative for stronger and more resilient health systems in the MENA region and the world over. In this paper, we introduce a tool designed to offer a comprehensive and engaging approach to assessing health system resilience and emergency preparedness and response capabilities, and articulate the tool’s value add in the MENA region.Methods We developed the tool following a three-step approach consisting of (1) definition of purpose and scope of tool, (2) item generation and reduction and (3) testing for content and face validity given the MENA region’s context. The Health System Resiliency Analysis Framework was adapted as the guiding framework for tool development.Results The tool offers a comprehensive and adaptable approach to self-assessment of health system resilience, using a multisectoral platform that enables continuous learning and improvement. The novelty of the tool resides in its potential to yield practical priority actions that need to be considered at all levels. The current version of the tool includes five components: (1) financing arrangements; (2) governance arrangements; (3) health system resources, public health and service delivery; (4) data and information systems; and (5) political and socioeconomic context. Each of the components consists of various subcomponents (22 in total). Each subcomponent is assessed using a mix of quantitative and qualitative indicators (99 indicators in total). On that basis, each subcomponent is scored to reflect the maturity of the country’s capacity in that specific area.Conclusion The proposed tool will address the limitations of the existing assessment instruments. We invite others to contribute with additional real-life implementation of the tool.